(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
The development of digital technologies and social media has led to the emergence of new forms of communication, one of which is the Internet meme. Memes have become an integral part of the contemporary media space and are actively used by individuals to convey information, express emotions, evaluate social phenomena, and create humorous effects. Today, Internet memes attract the attention not only of cultural scholars and sociologists but also of linguists, as they possess a complex linguistic structure and significant communicative potential.